1998
DOI: 10.1016/s0008-6363(98)00123-0
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular adenosine levels and cellular energy metabolism in ischemically preconditioned rat heart

Abstract: (i) Ischemic preconditioning reduces interstitial and vascular adenosine levels during ischemia-reperfusion, (ii) reduced ISF adenosine during ischemia is not due to reduced ischemic depletion of adenine nucleotides in preconditioned rat hearts, (iii) preconditioning may inhibit adenosine formation via 5'-nucleotidase in ischemic rat hearts, and (iv) improved functional recovery with preconditioning is unrelated to metabolic/bioenergetic changes during the ischemic insult, but may be related to improved post-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 46 publications
4
56
0
Order By: Relevance
“…Enzyme efflux tends to match functional outcome, being lowest in hearts displaying greater functional recovery. Consistently higher LDH versus CK efflux was observed, in agreement with our previous observations in the rat (Harrison et al 1998). Enzyme efflux data reveals an absence of significant tissue necrosis with 1&15 min of ischaemia in both isovolumic and apicobasally contracting models, with a pronounced increase in tissue damage as the period of ischaemia is increased to 220 min (Fig.…”
Section: Post-ischaemic Enzyme Leakagesupporting
confidence: 92%
See 2 more Smart Citations
“…Enzyme efflux tends to match functional outcome, being lowest in hearts displaying greater functional recovery. Consistently higher LDH versus CK efflux was observed, in agreement with our previous observations in the rat (Harrison et al 1998). Enzyme efflux data reveals an absence of significant tissue necrosis with 1&15 min of ischaemia in both isovolumic and apicobasally contracting models, with a pronounced increase in tissue damage as the period of ischaemia is increased to 220 min (Fig.…”
Section: Post-ischaemic Enzyme Leakagesupporting
confidence: 92%
“…The coronary circulation in the current model operates at -40'%1 of the peak flow of 45mlmin-' g-' (Headrick et al 2000h), and is responsive to varied stimuli. Although it has been suggested that crystalloid buffer may not adequately oxygenate inuriiie hearts and that added erythrocytes are required (Brooks & Apstein, 1996), the model exhibits the hallmarks of 02-sufficient tissue: ventricular pressure, heart rate and contractility are all high; the vasculature is sub-maximally dilated; substantial dilatation occurs during p-adrenoceptor or A2 adenosine receptor stimulation (Headrick et al 2000b); cellular energy state is high; myocardial purine and enzyme effluxes are low ( (Headrick et al 1998a), we estimate a AG,,, (the Gibbs free energy of ATP hydrolysis) of -61.4 kJ mol-I, exceeding the values for rat inyocardium (Harrison et al 1998;Headrick et al 1998b), and reflecting efficient oxidative ATP generation at the expense of ADP and P,.…”
Section: Normoxic Function and Stabilitymentioning
confidence: 53%
See 1 more Smart Citation
“…Thus, successively lower peak levels of adenosine were observed following each ischemia/reperfusion cycle. These findings were also observed by others (146)(147)(148)(149). It was suggested that the die away curve pattern of adenosine was due to diminished nucleotide decay induced by IP (146).…”
Section: Our Experimental Findingssupporting
confidence: 81%
“…Although calcium flux, 3 acidosis, 4 ATP depletion, 5 and reactive oxygen species 6 have been defined as putative causative factors, there may be other mediator factors that remain to be identified. Indeed, besides necrosis, apoptosis is one of the early events of either warm ischemia and reperfusion injury 7,8 or cold ischemia and reperfusion injury 2 in the heart.…”
Section: See Pmentioning
confidence: 99%